Costa Rica : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2013)
This article is a synopsis on Costa Rica's international spillovers, potential estimates, fiscal challenges, and banking systems. Spillovers are originated by cross-country trade and financial linkages, and also by the impact of global fiscal consolidation. The banking sector has about one-third foreign bank assets, and these foreign investments are controlled by the United States. So a shock in the United States or China will have adverse effects on Costa Rica. To have a medium- and long-term sustainability, Costa Rica needs to have some fiscal adjustments.